APLIKASI MONITORING PELAYANAN DAN FASILITAS PADA PUSKESMAS PAAL X: Aplikasi Monitoring;Puskesmas;UML (Unifiend Modeling Language);PHP;MySQL. - Purnama, Fery; Lisdarti; Silaen, Samuel (LP2M Universitas Nurdin Hamzah, 2021)
The service and facility monitoring application at the Paal X Health Center is a collection of complaints or messages from visitors regarding the services and facilities available at the Paal X Health Center. The Paal X Health Center does not yet have a complaint website that can input all complaints from visitors or patients seeking treatment at the Paal X Health Center. In designing the complaint information system at the Paal X Health Center, it contains input, process, and output on the complaint program that is run and modeled with UML (Unified Modeling Language) including Activity diagrams, use case diagrams, and sequence diagrams. The final result of this research is to produce a service and facility application design at the Paal X Health Center, where on this website visitors or patients can input their complaints or complaints about the services and facilities obtained during treatment and can view updated information from the Paal X Health Center. Monitoring application services and facilities at the Puskesmas were built using the PHP programming language with MySQL as the database.